Attenuation of Cardiovascular Responses to Direct Laryngoscopy and Intubation-A Comparative Study Between iv Bolus Fentanyl, Lignocaine and Placebo(NS) - Gurulingappa, (JCDR Research and Publications (P) Limited, 2012)
BACKGROUND AND OBJECTIVES: Laryngoscopy and tracheal intubation is invariably associated with a reflex sympathetic pressor response resulting in elevated heart rate and blood pressures. This may prove detrimental in high risk patients. Objective of this study is to compare the effects of lignocaine and fentanyl in attenuation of this pressor response to laryngoscopy and tracheal intubation. METHODS: Seventy five ASA I and II status normotensive patients scheduled for elective surgical procedures were selected randomly and divided into three groups of 25 each. All patients received premedication with pentazocine 0.05mg/kg i.v., atropine 0.01mg/ kg intramuscularly and midazolam 0.01mg/kg i.v. half an hour prior to induction. Induction of anesthesia was standardized for all patients who received, thiopentone 5 mg/kg i.v. and and were relaxed with succinylcholine 2mg/kg i.v. The first group received fentanyl 4micrograms/kg i.v bolus, the second group received lignocaine 1.5mg i.v bolus and then third group received placebo (normal saline), 5 minutes before laryngoscopy and intubation. HR, systolic, diastolic blood pressure were recorded noninvasively one day priorly B, Before induction 0 postinduction, 1,2,3,4 and 5 minutes from the onset of laryngoscopy. RESULTS: After intubation incidence of tachycardia (HR>100/min) was significantly greater in placebo and lignocaine group than in fentanyl group (p<0.05). Rise in SBP and DBP were also statistically significant in placebo and lignocaine group than in fentanyl group (p<0.05). CONCLUSION: Attenuation of pressor response is seen both with lignocaine and fentanyl. Of the two drugs fentanyl 4mgicrogram i.v. bolus provides a consistent, reliable and effective attenuation as compared to lignocaine 1.5mg/kg iv. bolus.